Reduction of serum cholesterol in hypercholesterolemic rats by Guar gum - Saeed Samarghandian; Mosa-; Atiyeh Sadat Davari; Marziyeh Abachi (Mashhad University of Medical Sciences, 2011)
Objective: Several diseases are reported to be uncommon in those parts of the world where dietary fiber intakes are high, therefore, in this study; we evaluated the hypocholesterolemiceffects of a dietary fiber (guar gum) in hypercholesteromic rats. Materials and Methods: Rats were fed high-fat or a normal fed diet for 12-week then treated with 5% guar gum in their regime during a 28 days period. Results: Total cholesterol was significantly increased in high-fat diet rats, while administration of guar gum significantly lowered it. Body weight was significantly increased in high-fat diet rats while, at the end of 4-weeks treatment of guar gum, body weight of treated rats was significantly decreased. Conclusion: These results suggested that guar gum may be effective as hypocholesterolemic agent and may prevent hypercholesteromia in hypercholesteromic rats. The results also suggested that guar gum may be important for reducing body weight in hyperlipidemic rats.